Next-Generation Technologies and Systems Biology for the Design of Novel Vaccines Against Apicomplexan Parasites - Tomazic, Mariela Luján; Marugan-Hernandez, Virginia; Rodriguez, Anabel Elisa (Frontiers in Veterinary Science, 2022)
Parasites of the phylum Apicomplexa are the causative agents of important diseases such as malaria, toxoplasmosis or cryptosporidiosis in humans, and babesiosis and coccidiosis in animals. Whereas the first human recombinant vaccine against malaria has been approved and recently recommended for wide administration by the WHO, most other zoonotic parasitic diseases lacks of appropriate immunoprophylaxis. Sequencing technologies, bioinformatics and statistics, have opened the ‘omics’ era into apicomplexan parasites, which has led to the development of systems biology, a recent field that can significantly contribute to more rational design for new vaccines. The discovery of novel antigens by classical approaches is slow and limited to very few antigens identified and analyzed by each study. High throughput approaches based on the expansion of the ‘omics’, mainly genomics and transcriptomics, has facilitated the functional annotation of the genome for many of these parasites, improving significantly the understanding of the parasite biology, interactions with the host, as well as virulence and host immune response. Developments in genetic manipulation in apicomplexan parasites have also contributed to the discovery of new potential vaccine targets. The present minireview does a comprehensive summary of advances in ‘omics’, CRISPR/Cas9 technologies, and in systems biology approaches applied to apicomplexan parasites of economic and zoonotic importance, highlighting their potential of the holistic view in vaccine development.